The properties of agroecosystems - Conway, Gordon R. (1987)
Agroecosystems may be regarded as true cybernetic systems whose goal is increased social value. This is achieved through a variety of strategies that combine different levels of productivity, stability, sustainability and equitability. Agricultural development thus involves making trade-offs between these properties. The point is illustrated by selected examples from agricultural history, including the origins of agriculture, manorial and modern western agriculture, and the Green Revolution in Indonesia. It is suggested that these properties may be used normatively as combined criteria for evaluating the performance of agricultural development programmes and projects.